IMPLEMENTASI HIDDEN CURRICULUM DALAM PEMBELAJARAN BAHASA INDONESIA UNTUK PENGUATAN KARAKTER DI SMP DAN SMA KHARISMA BANGSA - Siti Nurannisa; Lu’lu Naura Nur Syahidah; Nur Syamsiyah (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the implementation of the hidden curriculum in Indonesian language learning as an effort to strengthen students' character at Kharisma Bangsa Junior and Senior High School, Pondok Cabe, South Tangerang. The study employed a descriptive qualitative approach involving Indonesian language teachers and students at the junior and senior high school levels. Data were collected through observation, interviews, and documentation. The data were obtained from Indonesian language learning activities, group sharing programs, one on one mentoring, and school culture that supports students' character development. The findings reveal that the hidden curriculum is implemented through classroom discussions, literacy activities, teacher role modeling, individual mentoring, and parental involvement. These practices contribute to fostering students' discipline, responsibility, cooperation, empathy, self-confidence, and mutual respect. The findings indicate that Indonesian language learning not only functions to develop language competence but also serves as an effective medium for strengthening students' character education.